TRPV1: A promising therapeutic target for skin aging and inflammatory skin diseases - Xiao, Tengfei; Sun, Mingzhong; Zhao, Chuanxiang; Kang, Jingjing (Frontiers in Pharmacology, 2023)
TRPV1 is a non-selective channel receptor widely expressed in skin tissues, including keratinocytes, peripheral sensory nerve fibers and immune cells. It is activated by a variety of exogenous or endogenous inflammatory mediators, triggering neuropeptide release and neurogenic inflammatory response. Previous studies have shown that TRPV1 is closely related to the occurrence and/or development of skin aging and various chronic inflammatory skin diseases, such as psoriasis, atopic dermatitis, rosacea, herpes zoster, allergic contact dermatitis and prurigo nodularis. This review summarizes the structure of the TRPV1 channel and discusses the expression of TRPV1 in the skin as well as its role of TRPV1 in skin aging and inflammatory skin diseases.